GAMBARAN PENGELOLAAN SAMPAH RUMAH TANGGA TINJAUAN ASPEK PENDIDIKAN, PENGETAHUAN, DAN PENDAPATAN PERKAPITA DI RT 6 RW 1 KELURAHAN PEDURUNGAN TENGAH SEMARANG - Mifbakhuddin -; Trixie Salawati; Arif Kasmudi (Universitas Muhammadiyah Semarang, 2010)
Background: Rubbish is serious problem for society especially at urban affairs area. rubbish production at Semarang ill assorted with tool and the cleanliness manager infrastructure. This watchfulness is carried out at RT 6 RW 1 sub-district Pedurungan middle Semarang that be RT sample in household rubbish management by wet dustbin supplying and dry dustbin.Objective: Analyze corelation between education, erudition about household rubbish management, income perkapita with household rubbish managementMethod: Watchfulness observasional analytic this use research method and interview by means of help kuesioner. with approach cross sectional. population in this watchfulness entire subdistrict society member houses pedurungan middle RT 6 RW 1 numbers 33 houses. sample in this watchfulness total entire populasi(satisfied sample). big sample that taken in this watchfulness entire society member houses RT 6 RW 1 sub-district pedurungan middle semarang that numbers as much as 33 samples. free variable consists of education, member erudition about household rubbish management, income perkapita family. bound variable in this watchfulness is household rubbish management.Result: respondent education a large part SLTA as much as 20 respondents (60,6%). has erudition as big as 28 respondents (84,8%) about household rubbish management while good erudition, as big as 5 respondents (15,2%). income perkapita member a large part more thanstandard as big as 31 respondents (93,9%). a large part member rubbish management berkategori as big as 27 respondents (81,8%). statistics test shows there is no significant corelation between member education with rubbish management (p=0.096), there is no significant corelation between respondent erudition about rubbish management with rubbishmanagement (p=0,207), there is no significant corelation between income perkapita with rubbish management (p=0,141)Conclusion: there is no significant corelation between education, respondent erudition about rubbish management, income perkapita with household rubbish management.Keywords: education, erudition, income perkapita, household rubbish management